The Effect of Return on Asset, Debt to Equity Ratio, Audit Firm Reputation, and Audit Opinion on Audit Delay in Mining Companies Listed on the Indonesia Stock Exchange - Hakim, Alim Rahman; Winanti; Renlasrinara, Ira; Dewi, Putri Kumala (Journal of E-business and Management Science, 2024)
Audit delay refers to the length of time required to complete an audit, measured from the closing date of the fiscal year to the publication date of the audit report. This study aims to analyze the impact of profitability, leverage, audit firm reputation, and audit opinion on audit delay. Profitability in this study is measured by return on assets (ROA), while leverage is measured by the debt-to-equity ratio (DER). The sampling method used is purposive sampling, resulting in a sample of 13 mining sector companies listed on the Indonesia Stock Exchange from 2014 to 2018. Data analysis includes normality tests, classical assumption tests, and hypothesis testing using multiple regression methods. The results indicate that leverage, audit firm reputation, and audit opinion partially affect audit delay, while profitability does not. Simultaneously, profitability, leverage, audit firm reputation, and audit opinion significantly affect audit delay.